The Effect of Entrepreneurship Training, the Ability to Use Technology and Education on the Productivity of Women Entrepreneurs of UMKM - Dewi Sri; Clara Margareta (Program Studi Pendidikan Ekonomi, IKIP Budi Utomo Malang, 2020)
This study aims to prove the effect of training, skill in using technology, and level of education to productivity of women enterpreneur in Palembang. This study is conducted with quantitative method using primary data through a survey of women enterpreneur in Palembang. Totally 50 questionnaires are distributed to the women enterpreneur while there are only 42 (84%) complete questionnaires used in this study. The data analyses technique use validity, reliability, test of classical assumption, and hypothesis includes multiple linear regression analysis. The results of study indicate that the training of enterpreneur, the skill in using technology, and level of education gave effect to productivity. Determination Coefficient Test (R ²) shows Adjusted R Square of 0.783. This indicates that 78% of the Productivity variable can be explained by the variables of entrepreneurship training, ability to utilize technology, and education.